Determination of Color and Odor Preferences of Honey Bees (Apis Mellifera L.) - Yaşar Erdoğan; Kani Yavuz (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in the beekeeping research area of Bayburt University in order to determine the effect of odor and color on plant preference of honeybees in 2021. The experimental setup was established at a distance of 200 meters from the apiary where 80 Caucasian bees (Apis mellifera caucasica) colonies are located. As a result of the study, the most preferred feeders were the control group (pure sucrose syrup) (9.81 pieces), and the least preferred feeders were the rose-scent group (2.58). The effect of odor on honeybees' feed preferences varied according to months. Considering the effect of months on honeybees' visits to their feeders, the most visited feeders were Melissa (6.8) in June, control (11.69) in July, and control (14.58) in August. The highest number of feeder visits by honeybees was in August (9.24), and the lowest (2.89) in June. Considering the color preferences of honeybees, the most visited forage color was blue (5.98) and the least red was 4.89. The effect of colors on the feed preferences of honeybees also varied according to the months. The highest visitor bee average was found in the blue colored feeder (4.53) in June, the green colored feeder (7.24) in July, and the yellow and blue colored feeders (7.29) in August.